1998
DOI: 10.1016/s0002-9270(98)00591-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective case-cohort study of intestinal colonization with enterococci that produce extracellular superoxide and the risk for colorectal adenomas or cancer

Abstract: Significant associations were found for those with large adenomas or cancer (but not small adenomas), with age, and with foods enriched for vitamin A, vitamin E, and beta-carotene. An association between colonization with O2*--producing enterococci and colorectal adenomas or cancer, however, could not be ascertained, possibly because intestinal enterococcal flora changes over time, leaving a potentially cohesive hypothesis of colon cancer and risk factors as yet unanswered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…21 In a prospective study of fecal carriage, we found 64 (40%) of 159 samples tested positive for superoxide-producing enterococci. 25 Although we were unable to find any association between enterococcal colonization and the occurrence of large adenomas or CRC, we were surprised to find that colonization with enterococcal strains was not stable over time in this elderly cohort of subjects. This likely confounded our ability to detect an association.…”
Section: Bystander Effects and Commensal Bacteriamentioning
confidence: 67%
“…21 In a prospective study of fecal carriage, we found 64 (40%) of 159 samples tested positive for superoxide-producing enterococci. 25 Although we were unable to find any association between enterococcal colonization and the occurrence of large adenomas or CRC, we were surprised to find that colonization with enterococcal strains was not stable over time in this elderly cohort of subjects. This likely confounded our ability to detect an association.…”
Section: Bystander Effects and Commensal Bacteriamentioning
confidence: 67%
“…The potential oncogenicity of certain E. faecalis strains is further supported by observations that superoxide-producing E. faecalis induce marked distal colitis, DNA damage and cancer in germ-free Il10 −/− mice whereas superoxide-deficient E. faecalis induce inflammation but not tumor formation (Wang et al, 2012). Human data testing these concepts are limited to a prospective case cohort study of consecutive colonoscopy patients in which fecal E. faecalis populations were identified as unstable over >1 year and an association of superoxide-producing E. faecalis with detection of large colon adenomas or cancer was not found (Winters et al, 1998). …”
Section: Individual Microbes As Protagonistsmentioning
confidence: 99%
“…E. faecalis also encodes a metalloprotease, GelE, which contributes to the development of colitis, dysplasia and adenocarcinoma in monocolonized IL-10-deficient mice[87,111]. However, to date, a link between E. faecalis and human CRC has not been identified [112]. …”
Section: Other Animal Models Of Bacterial Influences On Crcmentioning
confidence: 99%